2014
DOI: 10.5430/crim.v1n2p187
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal atresia and hypertrofic pyloric stenosis: An association to consider

Abstract: Esophageal atresia (EA) with distal tracheosophageal fistula (TEF) develops hypertrophic pyloric stenosis (HPS) during the late postoperative period with a described prevalence of 1%-10%.The aim of this retrospective study is to show our experience in this association and to report two specific cases. Of 61 patients with EA treated in our institution, 2 developed HPS. Both cases underwent a Ramstedt extramucosal pyloromyotomy. Currently, patients are asymptomatic.Our frequency (3.3%) is similar to other public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Foster and Shaw13 reported the association between OA and HPS for the first time in 1946. Palacios  et al 6 reported HPS in 3.3% of 61 patients they operated due to OA. van Beelen et al 4 reported HPS in 7.5% of 267 patients who underwent surgery for OA.…”
Section: Discussionmentioning
confidence: 98%
“…Foster and Shaw13 reported the association between OA and HPS for the first time in 1946. Palacios  et al 6 reported HPS in 3.3% of 61 patients they operated due to OA. van Beelen et al 4 reported HPS in 7.5% of 267 patients who underwent surgery for OA.…”
Section: Discussionmentioning
confidence: 98%